DISSEMINATION OF URBAN ORGANIC WASTE TREATMENT TECHNOLOGY INTO ORGANIC FERTILIZERS FOR THE DEVELOPMENT OF URBAN AGRICULTURE: DISEMINASI TEKNOLOGI PENGOLAHAN LIMBAH ORGANIK PERKOTAAN MENJADI PUPUK ORGANIK UNTUK PENGEMBANGAN PERTANIAN KOTA - Dwi Haryanta; Tatuk Tojibatus Sa’adah; Mochamad Thohiron (Yayasan Education and Social Center, 2022)
The urban development program will have consequences for the generation of waste. Urban organic waste includes forest/city park plant waste, market waste, and household waste. Urban organic waste in the Jambangan village environment causes environmental and social problems. Community empowerment activities at the “Satu Padu” farmer group, Jambangan Village, Surabaya aim to provide knowledge about managing harmful organic waste that is processed into compost and liquid organic fertilizer that is beneficial in urban farming practices. The community empowerment program in managing tree stumps waste uses the Participatory Rapid Rural Appraissal and Rapid and Rural Appraissal methods. Inventory of problems and formulation of solutions is carried out in a short time but studies are carried out in depth and the community is directly involved in the preparation of implementation plans and evaluation of activities. Community The farmer group “One Solid”, Jambangan Village, Surabaya is very enthusiastic in implementing the program. The residents and farmer groups were coordinated directly by the Village Head and the Head of the Farmers Group directly practiced the technology that was disseminated, namely making compost from tree stumps waste, making liquid organic fertilizer from fruit and vegetable waste and planting using media with compost and plants being given liquid organic fertilizer